2021
DOI: 10.3390/healthcare9111593
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of the Free COVID-19 Telephone Consultations Available during the First Wave of the Pandemic in Japan

Abstract: This cross-sectional study aimed to (1) describe the unclassified contents of telephone consultation services provided by a public health center during the first wave of COVID-19 in Japan and (2) examine whether the contents required assistance from public health nurses (PHNs). We analyzed a total of 207 calls in which the purpose of the call was unclassified into pre-set categories. PHNs transcribed the exact text of the consultation conversations recorded from 25 March to 20 April 2020 in City A. Approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…PHN identified tasks, including contact tracing, health monitoring, hospitalisation coordination and consultation with residents, to be shifted onto part-time PHN and other nursing and support staff to forestall organisational dysfunction [45]. Similarly, analysis of teleconsultations by PHN during the first infection wave by Yoshioka-Maeda et al [46] showed that conversations were majorly about prevention measures and referral pathways, which PHN need not have attended. Managers were advised to let PHN handle essential consultations and shift teleconsultations onto low-level staff and office workers by developing script-based manuals and proper training.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PHN identified tasks, including contact tracing, health monitoring, hospitalisation coordination and consultation with residents, to be shifted onto part-time PHN and other nursing and support staff to forestall organisational dysfunction [45]. Similarly, analysis of teleconsultations by PHN during the first infection wave by Yoshioka-Maeda et al [46] showed that conversations were majorly about prevention measures and referral pathways, which PHN need not have attended. Managers were advised to let PHN handle essential consultations and shift teleconsultations onto low-level staff and office workers by developing script-based manuals and proper training.…”
Section: Discussionmentioning
confidence: 99%
“…This will help reduce mortality, morbidity, stressors and burn outs. PHN at Japanese public health centers shifted teleconsultations onto office staff as discussed previously [46] Yoshioka-Maeda [51] reported PHN developing web-based data systems to exchange COVID-19 patient information and shift hospital coordination and clerical tasks to office staff, and inventory management, including management of personal protective to external companies. TS through web-based systems saved nursing time, decreased workloads and improved efficiency in allocating supplies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teleconsultations by PHN during the first wave focused on prevention measures and referral pathways, prompting managers to shift these tasks to lower-level staff and office workers using scripted manuals. This allowed PHN to concentrate on infection control and management [44]. In Ghana, the central teaching hospital adapted staff roles and schedules to transfer medication prescribing and ART dispensing from pharmacists to nurses, ensuring ART continuity and reducing patient waiting times at HIV clinics [54].…”
Section: Health Workforcementioning
confidence: 99%
“…In Japan, dedicated virtual consultation services were introduced early in the pandemic through the Japanese Infectious Disease Prevention Act, where public health centers became responsible for infectious disease control and prevention ( 55 , 56 ). An improved version of teleconsultation service, supported by the local government, was reported in Hiroshima city, and included a hotline for COVID-19 center available 24-hours a day, providing online consultation in 10 languages.…”
Section: Access To Carementioning
confidence: 99%